Lagerstätte effect drives notosuchian palaeodiversity (Crocodyliformes, Notosuchia). (2nd November 2021) - de Celis, A.; Narváez, I.; Arcucci, A.; Ortega, F.
ABSTRACT: Notosuchians are a crocodyliform clade with a rich Gondwanan fossil record, especially in Cretaceous South American deposits. More than half of all described species come from South America and, around one quarter, have been discovered in the Adamantina Formation (Bauru Group, Brazil). The large amount of notosuchian remains from this formation, along with its chronostratigraphic uncertainty, may be distorting notosuchian palaeodiversity estimates. In order to analyse how these factors could be biasing our interpretations, palaeodiversity estimates were performed excluding and including the Adamantina Formation occurrence data, as well as assigning them to the main age ranges that have been proposed for the formation (Turonian-Santonian and Campanian-Maastrichtian). Furthermore, as other factors might be influencing palaeodiversity fluctuations, a modelling approach was performed to assess which abiotic factors, sampling artefacts, or a combination of them, could be driving these palaeodiversity dynamics. The results showed that the Adamantina Formation is causing a Lagerstätte effect that is distorting palaeodiversity estimates and, depending on the age assigned to that formation, the tempo and magnitude of the maximum palaeodiversity reached during the Late Cretaceous substantially changes. The results also suggest that the temporal bias might affect palaeobiological reconstructions not only in notosuchians but also in other groups. Abstract : uf0001